2012
DOI: 10.1111/j.1365-2435.2012.01962.x
|View full text |Cite
|
Sign up to set email alerts
|

Stem xylem conductivity is key to plant water balance across Australian angiosperm species

Abstract: 1. Plants must balance water expenditure from their crown with water supplied through root and stem tissues. Although many different combinations of hydraulic traits could accomplish water balance, we ask whether variation across species in stem hydraulic traits has been concentrated along few, or many, dimensions of trait variation. 2. We measured stem hydraulic traits for 120 woody dicot species across a range of different biomes in eastern Australia. Mean annual temperatures ranged from 10 to 27 °C and arid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
109
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(120 citation statements)
references
References 57 publications
(108 reference statements)
10
109
0
1
Order By: Relevance
“…In our study, higher stem capacitance was associated with higher fractions of vessels (Figure d). The high vessel fraction could contribute to high transport efficiency (Gleason et al, ). However, using a data set collected from chaparral shrubs growing at field sites in southern California, Pratt and Jacobsen () found no relationship between stem capacitance and stem‐specific conductivity.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, higher stem capacitance was associated with higher fractions of vessels (Figure d). The high vessel fraction could contribute to high transport efficiency (Gleason et al, ). However, using a data set collected from chaparral shrubs growing at field sites in southern California, Pratt and Jacobsen () found no relationship between stem capacitance and stem‐specific conductivity.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional views of hydraulic limitation include (1) declines in leaf area-specific hydraulic conductance with increasing tree height; (2) declines in w leaf with tree height due to decreased whole-plant hydraulic conductance and increased gravitational potential; and (3) resulting decreases in average stomatal conductance (Ryan and Yoder 1997, Koch et al 2004, Ryan et al 2006, Hinckley et al 2011, Mencuccini et al 2011. Factors that might contribute to a tighter relationship of maximum tree height to P/E p than expected based on hydraulic limitation (and thus D) alone might include (4) increased allocation to leaves vs. roots or stems at a given height with increasing P/E p , or conditions correlated with higher P/E p (e.g., greater soil silt or nitrate content); (5) higher photosynthetic rates per unit leaf mass at higher P/E p or under conditions correlated therewith, independent of the degree of stomatal limitation; (6) higher leaf area-specific conductance at higher P/E p in trees of a given height, reflecting differences in wood density and xylem diameter and length (Thomas 1996b, Thomas and Bazzaz 1999, Zach et al 2010, Fan et al 2012, Gleason et al 2012; (7) variation across species in the rate at which mesophyll photosynthetic capacity declines with decreasing w leaf (Givnish 1986, Tezara et al 2003, Lawlor and Tezara 2009); (8) variation across sites in which the rate at which evaporation from sunlit leaves increases with relative height at the top of the canopy; and (9) greater uncertainties in measuring average D than average height. The preceding factors are all plausible ways in which resource allocation or modified hydraulic limitation effects could constrain tree height along the Victoria transect, in response to the increase in P/E p toward the Yarra Ranges, the reduced heat load and cloudier conditions at higher altitudes and latitudes there, and the increasingly fine-grained, more P-and Nrich soils there (see Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Moister, more fertile conditions should favor species with higher SLA, leaf N concentration per unit mass, stomatal conductance, D, leaf hydraulic conductance, and maximum photosynthetic rate per unit leaf mass, and lower percentage root allocation and wood density, with the latter leading to high values of stem hydraulic conductance. Indeed, in a recent analysis of gasexchange and hydraulic traits in 120 dicot species along an aridity gradient in eastern Australia, Gleason et al (2012) showed that plant height increased with xylemspecific hydraulic conductivity normalized by the ratio of total leaf area to total xylem area. The relationships observed accounted for 39% of height and conductivity differences within sites, but only 10% of the variance across sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations